Effect of Cdc42 on myocardial ischemia-reperfusion of rats - Xu, X.; Kong, L.; Song, X.; Hao, Z.; Yuan, F. (Cellular and Molecular Biology, 2017)
To investigate the effects and their possible mechanisms of cell division cycle 42 (Cdc42) to neonatal rat myocardial cells subjected to the ischemia-repefusion. Neonatal rat cardiomyocytes were cultured and then subjected to the ischemia-reperfusion. Experimental groups 1. Control group; 2. Ischemia-repefusion group (I/R group); 3. Oligofectamine group (Oli group); 4. Oligofectamine and antisense oligodeoxynucleotide (AS-ODN) group (As group); 5. Oligofectamine and missense oligodeoxynucleotide (MS-ODN) group (Ms group); 6. SP600125 and Oligofectamine and AS-ODN group (SP600125/As group); 7. SP600125 and Oligofectamine and MS-ODN group (SP600125/Ms group). The cardiacmyocyte apoptosis rate was detected by AnnexinV/PI with flow cytometry. Cdc42, JNK, p-JNK, Bax and Bcl-2 were detected by western blot. In comparison with control group, Cdc42, the cardiacmyocyte apoptosis rate and phosphorylation of JNK were increased and the ratio of Bcl-2/Bax was reduced in the I/R group; Cdc42, the cardiacmyocyte apoptosis rate and phosphorylation of JNK in As group was lower than the I/R group, Oli group and the Ms group, and the ratio of Bcl-2/Bax was the highest in the four groups; Cdc42, cardiacmyocyte apoptosis rate, phosphorylation of JNK and the ratio of Bcl-2/Bax showed no differences in the I/R group, Oli group and the Ms group. Compared with As group, phosphorylation of JNK was lower in the SP600125/As group, phosphorylation of JNK in SP600125/Ms group was lower than the Ms group, and it showed no differences between the SP600125 & As group and the SP600125 & Ms group. Cdc42 in myocardial I/R can promote cardiacmyocyte apoptosis rate. AS-ODN of Cdc42 can decrease the cardiacmyocyte apoptosis rate in I/R. Cdc42 may played a role in myocardial I/R via JNK , Bcl-2 and Bax signal pathway.